ANATOMICAL AND PHYSIOLOGICAL CHARACTERISTICS OF HEMATOPOIETIC ORGANS IN CHILDREN AND ADOLESCENTS. PERIPHERAL BLOOD COMPOSITION IN DIFFERENT AGE GROUPS. SEMIOTICS AND SYNDROMES OF HEMATOPOIETIC SYSTEM DISORDERS IN CHILDREN - Radjabova Sabina; Turdiyev Shuhrat Berdiyevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article describes the anatomical and physiological characteristics of hematopoietic organs in children and adolescents. Changes in the composition of peripheral blood in children of different age groups, specific features of the hematopoiesis process, and stages of development of the hematopoietic system are analyzed. In addition, diseases caused by dysfunction of hematopoietic organs in children, their clinical manifestations, semiotics, and diagnostic significance are discussed. The article serves as an important theoretical source for students studying pediatrics.